Two-dimensional organic–inorganic hybrid perovskite ferroelastics: (PEA)2[CdCl4], (3-FPEA)2[CdCl4], and (4-FPEA)2[CdCl4]. Issue 8 (31st January 2023) - Yue, Zhi-Yuan; Luo, Wang; Wang, Na; Li, Hua-Kai; Xu, Ze-Jiang; Feng, Yan; Shi, Chao; Ye, Heng-Yun; Miao, Le-Ping
Abstract : Three 2D organic–inorganic hybrid perovskites ferroelastics with dielectric switch. This work provides a new case for the preparation of 2D perovskite ferroelastic materials and the possibility for the application in actuators. Abstract : As a mechanical analog of ferroelectricity and ferromagnetism, ferroelasticity has made outstanding contributions in the fields of energy conversion, information processing, and mechanical switching. However, research on 2D ferroelasticity is lacking so far, and it is still a challenge to synthesize 2D perovskite ferroelastics. Here, we successfully constructed three 2D organic–inorganic hybrid ferroelastics: (PEA)2 CdCl4 [PEA = phenethylamium cation, 1 ], (3-FPEA)2 CdCl4 [3-FPEA = 3-fluorophenethylamium cation, 2 ] and (4-FPEA)2 CdCl4 [4-FPEA = 4-fluorophenethylamium cation, 3 ]. These compounds undergo a structural phase transition between 379–385 K, exhibit temperature-triggered ferroelasticity, and possess a dielectric transition. The structural analysis of temperature-variable single crystals indicates that the reason for the phase transition of the ferroelastics is the order–disorder transition of cations and distortion of the anion framework. This research provides new options for a new generation of 2D perovskite ferroelastics.